The Glow Still Shows: Effects of Facial Masking on Perceptions of Duchenne Versus Social Smiles. (August 2021) - Sheldon, Kennon M.; Goffredi, Ryan; Corcoran, Mike
Facial expressions of emotion have important communicative functions. It is likely that mask-wearing during pandemics disrupts these functions, especially for expressions defined by activity in the lower half of the face. We tested this by asking participants to rate both Duchenne smiles (DSs; defined by the mouth and eyes) and non-Duchenne or "social" smiles (SSs; defined by the mouth alone), within masked and unmasked target faces. As hypothesized, masked SSs were rated much lower in "a pleasant social smile" and much higher in "a merely neutral expression, " compared with unmasked SSs. Essentially, masked SSs became nonsmiles. Masked DSs were still rated as very happy and pleasant, although significantly less so than unmasked DSs. Masked DSs and SSs were both rated as displaying more disgust than the unmasked versions.